2010
DOI: 10.1134/s0006297910020045
|View full text |Cite
|
Sign up to set email alerts
|

New-generation Skulachev ions exhibiting nephroprotective and neuroprotective properties

Abstract: A mitochondria-targeted chimeric compound consisting of a rhodamine derivative linked to a plastoquinone molecule (10-(6'-plastoquinonyl)decylrhodamine, SkQR1) was studied under conditions of acute brain or kidney damage. A protective effect of this compound was demonstrated in a model of focal brain ischemia, rat kidney ischemia/reperfusion, myoglobinuria (rhabdomyolysis, or crush syndrome), and pyelonephritis. We found that a single intraperitoneal injection of SkQR1 diminishes the size of the ischemic zone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 25 publications
0
26
0
2
Order By: Relevance
“…It was shown that SkQR1 can effectively protect the brain and kidney from ischemia injuries that are accompanied by generation of ROS (54,55). It has recently been shown that C 12 R1 can FIGURE 9.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that SkQR1 can effectively protect the brain and kidney from ischemia injuries that are accompanied by generation of ROS (54,55). It has recently been shown that C 12 R1 can FIGURE 9.…”
Section: Discussionmentioning
confidence: 99%
“…(SkQR1). Another study reported the nephroprotective action of SkQR1in two animal models of kidney failure (ischemia, rhabdomyolysis) and in an in vitro setting of pyelonephritis (243), as well as a neuroprotective role in a rat model of focal brain ischemia (243). Importantly, C12R, a conjugate of rhodamine with a linker chain of 12 carbon atoms, did not exhibit neuroprotective effects in this model of stroke, thereby showing that this biological activity could not be attributed to the part of the molecule not carrying the quinone residue.…”
mentioning
confidence: 99%
“…Mitochondria and NADPH oxidases (19) are the two principle sources of ROS although their relative contribution to inflammatory pathologies is not well-defined. A new class of antioxidants that specifically target mitochondrial ROS (hereafter referred to as SkQ1 and SkQR1) have been recently developed and shown to have a beneficial effect in a number of cell pathologies (20)(21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%